Minimally invasive management of a giant paratubal cyst in an adolescent female: Case report and review of the literature in the pediatric population - Romeo, Paola; Loria, Giada; Martinelli, Canio; Ercoli, Alfredo; Romeo, Carmelo (Frontiers in Pediatrics, 2022)
Introduction: Paraovarian or paratubal cysts both define cysts located between the ovary and the fallopian tube. They are usually benign and frequently occur in the third and fourth decade of life. Paratubal cysts are defined as giant when they exceed the threshold of 150 mm. Methods: We report the case of a 15-years-old girl complaining about diffuse abdominal pain since two years that was diagnosed with a 196x90x267mm giant paratubal cyst. We furthermore reviewed all the articles published on thirteen articles, published between 2006 and 2021, all concerning giant POC in paediatric patients. Results: The giant mass of our 15-years-old patient was removed through a fertility-sparing laparoscopic surgery. Histopathological diagnosis of cystadenomafibroma was made up, with no cytologic report of neoplastic cells. The incidence of POC in the pediatric and adolescent population attests around 4 %. However, only 12.96% of them is defined giant (larger than 15 cm). Indeed, to the best of our knowledge, only thirteen cases of giant paratubal cysts have been reported in adolescents. To accomplish diagnosis and differential diagnosis, accurate history and physical examination are mandatory. In all cases reported in the literature, further instrumental analyses were performed, including ultrasound, CT and/or MRI scan. International Ovarian Tumor Analysis (IOTA) rules have not yet been validated in the pediatric population. Because of the advantages of the laparoscopic procedures, it is often preferred in pediatric population, also to help preserving as much ovarian parenchyma and salpinx if thought possible. The incidence of malignant adnexal masses in pediatric population it is reported to range from 4% to 9%, accounting for 1% of all pediatric cancers. Conclusion: Giant paratubal cysts in adolescent females are extremely rare and usually benign. A fertility-sparing laparoscopic surgery should be the preferable option whenever possible. Considered the rarity of these conditions, further investigations are needed to exclude the possibility of a malignant evolution.